NATURAL RESISTANCE AGAINST INSECT PESTS IN COTTON - Z. M. Din; T. A. Malik; F. M. Azhar; M. Ashraf (Journal of Animal and Plant Sciences, 2016)
Insect pest infestation is a major constraint in cotton production and causes heavy yield losses every year. Some studies report that insect pests attack on genotypes/cultivars with the traits, frego bracts, okra leaf, and red leaf color is comparatively lower. Genotypes/cultivars having these traits were assessed for insect pest infestation in comparison to commercial cultivars which did not contain these traits. Experimental plots were separated by fine netting to confine insect pests within the genotype/cultivar. The Gossypium arboreum cultivar,FH-170, had lower population buildup of sucking and chewing insect pests. In general, among the G. hirsutum genotypes/cultivars, lowest population buildup of jassid, white fly, spotted bollworm and American bollworm was found on Gumbo Okra (okra leaf). Minimum aphid was recorded on Russian Red (red leaf color). PBG-Fb-5 (frego bract) showed the most resistant response against pink bollworm. Population buildup of thrips, mites and aphid was relatively higher under water deficit conditions compared to well water conditions whereas, population buildup of jassid, and white fly was higher under well watered conditions.
Keywords: Okra Leaf Cotton; Frego Bract Cotton; Red Leaf Color Cotton; Insect Pests; Relative Water Contents of Cotton leaf